2008
DOI: 10.1111/j.1469-7610.2008.01932.x
|View full text |Cite
|
Sign up to set email alerts
|

A developmental model of maternal and child contributions to disruptive conduct: the first six years

Abstract: Examination of developmental links among early maternal behavior, the child's responsive stance toward the mother, conscience, and disruptive behavior is a promising step toward elucidating mechanisms of children's adaptive and maladaptive trajectories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 38 publications
7
52
0
1
Order By: Relevance
“…Studies have shown that girls growing up without the presence of their father are prone to develop internalizing problems (see Parke et al, 2002), but little has been said about the positive aspects of the presence of a father for daughters or the developmental mechanisms by which these positive effects may occur. Paternal warmth may have particular importance for girls in the development of emotional responding to others (Kochanska et al, 2008;) and in stress regulation (Byrd-Craven et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that girls growing up without the presence of their father are prone to develop internalizing problems (see Parke et al, 2002), but little has been said about the positive aspects of the presence of a father for daughters or the developmental mechanisms by which these positive effects may occur. Paternal warmth may have particular importance for girls in the development of emotional responding to others (Kochanska et al, 2008;) and in stress regulation (Byrd-Craven et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Warmth is a component of sensitivity and captures the positive affective quality of the relationship. It has been argued that parental warmth may have an indirect effect on children's social outcomes through the development of emotional responding and internalization of positive reciprocal relationships (Kochanska et al, 2008;. Others have argued that warmth is associated with authoritative parenting (Udin, 2011), which in turn is associated with positive outcomes (Steinberg, 2001).…”
Section: Father Warmth and Sensitivitymentioning
confidence: 98%
“…Further, evidence indicates that favorable rearing behaviors such as responsiveness, care and warmth foster the development of adaptive self-conscious emotions like guilt (see e.g. the work of Kochanska et al 2005; 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Internalization of parental rules has been studied in young children as the ability to abstain from wrongdoing and the development of conscience. Kochanska and colleagues have published extensively on this topic, demonstrating consistently and repeatedly that a child's ability to internalize parents' rules and successfully demonstrate conscience is directly related to the parent-child relationship and to maternal responsivity (e.g., Kochanska, 1994;Kochanska & Aksan, 2004Kochanska, Barry, Aksan, & Boldt, 2008). The emphasis in this work and others like it (e.g., Laible, 2004aLaible, , 2004b has been on the relation between a warm, nurturing social environment and not only compliant and caring behavior in children but also the desire to comply with parental requests (Grusec & Goodnow, 1994).…”
Section: Concern For Othersmentioning
confidence: 99%